Cardiac arrest associated with non-toxigenic corynebacterium diphtheria strain: A case report - Alvarez, George V.; Rupert, Deborah D.; Sinclair, Samantha; Miyara, Santiago J.; Guevara, Sara; Shih, Peter; Hoey, Cynthia (Frontiers in Medicine, 2023)
Here we document a rare, acute, infection caused by non-toxigenic Corynebacterium diphtheriae and the resulting unique and severe clinical sequelae. Our patient was a young man with no known pre-existing conditions that presented in cardiopulmonary arrest. We contrast this case with prior instances of non-toxigenic C. diphtheriae strain infection in the United States and summarize the literature that suggests systemic infection can result in cardiogenic toxicity. We speculate on a possible missed, pre-existing condition that could have increased this patient’s susceptibility to poor clinical outcome.